The Impact of Fertility on Family Welfare - Alya Ardhina Putri; Putri Estefania; Intan Pramunita; Siti Asriyah; Agung Prabowo (Research Collaboration Community (RCC), 2022)
Family welfare is considered not going well since the Covid-19 pandemic, one of the factors for family welfare is fertility. Therefore, we conducted a study aimed at analyzing the impact of high fertility on family well-being. This research is descriptive quantitative with the number of respondents as many as twenty people. Data was obtained by survey method through Google Form where 20 respondents had to answer a list of structured questions (constructed questionnaire). The results showed that the number of children did not affect the welfare of the family.